Variable Unidentate Ligands in Cu(I)(XXY) and Cu(I)(XYZ) Complexes—Structural Aspects - Milan Melník; Veronika Mikušová; Peter Mikuš (Inorganics, 2025)
This manuscript provides a structural analysis of over eighty copper(I) compounds mostly reported in the Cambridge Structural Database (CSD) version 5.45 in which unidentate ligands build up various inner coordinate spheres. These complexes crystallized in four crystal classes: trigonal (1 example), triclinic (10 examples), orthorhombic (13 examples), and monoclinic (58 examples). The analyzed complexes can be divided into two groups according to the type of coordinating ligands (L = X, Y, Z) incorporated into their structure: Cu(XXY) (more common) and Cu(XYZ). The structural data of L-Cu-L bond angles show that the angular distortion from the regular trigonal geometry grows with total mean values of deviation from 120.0°, in the order within the first group: 3.2°(Cu(IIP)) < 6.1°(Cu(ClClY)) < 6.5°(Cu(SSY)) < 8.2°(Cu(PPY)) < 8.9°(Cu(BrBrY)) < 16.9°(Cu(NNY)) < 19.8°(Cu(CCY)) < 25.5°(Cu(SeSeY)) and within the second group: 3.1°(Cu(SIP)) < 14.3°(Cu(SClP) < 15.5°(Cu(SBrP). The donor atoms are responsible for the distortion as follows: the soft donor atoms diminish the distortion while the borderline and the hard growing amplify the distortion. Given the importance of Cu(I) compounds in (bio)inorganic functional materials and catalysis, the correct interpretation of the geometry of Cu(I) complexes in terms of the coordination polyhedra is crucial for understanding the properties of the respective compounds.